Treating eating disorders in groups: A pilot study on the role of a structured intervention on perfectionism on group climate. Issue 2 (31st July 2021) - Margherita, Giorgia; Gargiulo, Anna; Gaudioso, Rosita; Esposito, Giovanna
Abstract: Several studies have shown the efficacy of group treatments for patients with eating disorders (EDs) who have negative attitudes towards their bodies, also using the group climate as an indicator of process. Within this field of study, perfectionism has been examined as a factor that maintains eating disorders. This study proposes to comprehend what kind of treatment favours a better group climate, by providing a within‐person comparison between two short group treatments of ED patients, where one was not focused on a specific topic and the other was structured around the topic of clinical perfectionism. Two groups of young adult patients with eating disorders were monitored for three months. Group climate was measured both with the Group Climate Questionnaire, which was administered at the end of each session, and through the clinical accounts written by an observer. The findings revealed that the perfectionism group, in comparison with the control group, presented a significantly higher level of engagement and avoidance, along with a lower level of conflict. In particular, the engagement of the perfectionism group increased in accordance with the therapeutic process, whilst in the control group, it remained relatively constant. The conflict decreased in both groups whilst avoidance increased alongside the sessions of the perfectionism group and decreased in the control group. The group on perfectionism, despite its enhanced high levels of avoidance, was effective in promoting a positive group climate. The clinical implications of structured group treatment for eating disorders, which manage the theme of mind‐body splitting, will be discussed.